Pollen Allergies in Humans and their Dogs, Cats and Horses: Differences and Similarities. Issue 1 (7th April 2015) - Jensen‐Jarolim, Erika; Einhorn, Lukas; Herrmann, Ina; Thalhammer, Johann G; Panakova, Lucia
Abstract: Both humans and their most important domestic animals harbor IgE and a similar IgE receptor repertoire and expression pattern. The same cell types are also involved in the triggering or regulation of allergies, such as mast cells, eosinophils or T‐regulatory cells. Translational clinical studies in domestic animals could therefore help cure animal allergies and at the same time gather knowledge relevant to human patients. Dogs, cats and horses may spontaneously and to different extents develop immediate type symptoms to pollen allergens. The skin, nasal and bronchial reactions, as well as chronic skin lesions due to pollen are in principle comparable to human patients. Pollen of various species most often causes allergic rhinitis in human patients, whereas in dogs it elicits predominantly eczematous lesions (canine atopic dermatitis), in horses recurrent airway obstruction or hives as well as pruritic dermatitis, and in cats bronchial asthma and so‐called cutaneous reactive patterns (eosinophilic granuloma complex, head and neck pruritus, symmetric self‐induced alopecia). In human allergy‐specific IgE detection, skin tests or other allergen provocation tests should be completed. In contrast, in animals IgE and dermal tests are regarded as equally important and may even replace each other. However, for practical and economic reasons intradermal tests are most commonly performed in a specialized practice. As in humans, in dogs, cats and horses allergen immunotherapy leads to significant improvement of the clinical symptoms. The collected evidence suggests that canines, felines and equines, with their spontaneous allergies, are attractive model patients for translational studies.